Bleeding complications drive early mortality of patients with atrial fibrillation after transcatheter aortic valve replacement. (25th November 2020) - Stachon, P; Lother, A.L; Kaier, K.K; Zehender, M.Z; Bode, C.B; Von Zur Muehlen, C.M
Abstract: Background and objectives: Atrial fibrillation is a risk factor for poor post-operative outcome after transfemoral transcatheter aortic valve replacement (TF-TAVR). The present study analyses the outcomes after TF-TAVR in patients with or without atrial fibrillation (AF) and identifies independent predictors for in-hospital mortality in clinical practice. Methods and results: Among all 57, 050 patients undergoing isolated TF-TAVR between 2008 and 2016 in Germany, 44.2% of patients (n=25, 309) had AF. Patients with AF were at higher risk for unfavorable outcome after TAVR. Including all baseline characteristics for a risk-adjusted comparison, AF was an independent risk factor for in-hospital mortality after TAVR. Among patients with AF, EuroSCORE, NYHA class or renal disease had only moderate effects on mortality, while the occurrence of post-procedural stroke substantially increased in-hospital mortality (OR 3.55, 95% CI 2.77–4.56, P<0.001). However, the strongest independent predictor for in-hospital mortality among patients with AF was bleeding (OR 11.04, 95% CI 9.53–12.80, P<0.001). Bleeding also was by far the strongest predictor for prolonged mechanical ventilation (OR 25.36, 95% CI 21.83–29.48, P<0.001). Conclusions: The present study demonstrates that the incidence of bleeding defines the early outcome of patients with AF after TF-TAVR. Thus, the peri-procedural phase demands particular care in anti-thrombotic regimen. Funding Acknowledgement: Type of funding source: None